Short communication Phenol contaminant of Bengawan Solo River and characteristics of Portulaca using flavonoid, saponin, and tannin for phytoremediation purposes (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Khoiriyah S, Gravitiani E, Setyono P, Suranto. 2019. Short communication Phenol contaminant of Bengawan Solo River and characteristics of Portulaca using flavonoid, saponin, and tannin for phytoremediation purposes. Biodiversitas 20: 3269-3274. Bengawan Solo River (BSR) as one of the largest river in Java has been contaminated by several waste products including industrial activities and organic materials produced by households along the edge of river. One of the very dangerous substances was Endocrine Disrupting Compound (EDC). This estrogenic waste solution has been considered to have a negative impact on the environmental conditions which could cause quality water becoming worse. The aims of this research were to identify the quality BSR whether or not contaminated by phenol and to reduce the very potential pollutants of EDC by introducing local native plants of Portulaca species as a candidate of phytoremediation plant agents. To characterize the three species of Portulaca, i.e. P. oleracea, P glandiflora, and P. pillosa, TLC-test to detect their flavonoid, saponin, and tannin were conducted respectively. Accordingly, HPLC was used to detect the presence of EDC. The results showed that BSR’s EDC has been detected with a concentration of 0,0013 ng. Also, all three species of Portulaca contained flavonoid, tannin, and saponin, in which the highest concentration of saponin has been detected in P. pillosa. Based on these results, it is expected that plants containing the highest secondary metabolism, such as saponin would be very promising to be used for phytoremediation purposes. The preliminary result of HPLC showed supporting this prediction.
Keywords: Bengawan Solo River, estrogenic, EDC, phytoremediation, Portulaca